Fighting tuberculosis hand in hand: A call to engage communities affected by TB as essential partners in research. - N Venkatesan; L Faust; R Lobo; H Enkh-Amgalan; T Kunor; Z Sifumba; S Rane; K O'Brien; B Kumar; C N Maimbolwa; M Mayta; H Patel; et al. (PLOS Global Public Health, 2025)
Tuberculosis (TB) is an infectious disease closely intertwined with stigma, discrimination, and the social determinants of health. Communities of people affected by TB are experts in their care pathways, but the TB field continues to fall short of meaningfully engaging communities in TB research. This is a missed opportunity to improve the quality, relevance, person-centeredness, positive impact, and sustainability of TB research outputs. We acknowledge the important progress that has been made to date regarding community engagement in TB, but emphasize persisting barriers to meaningful engagement, and the urgent need for updated and comprehensive TB-specific standards for such engagement in research. We highlight that core components of these standards should include the mobilisation of communities affected by TB, bilateral training in community engagement (for researchers and communities), as well as ensuring appropriate remuneration, representation of priority groups, and the use of non-stigmatising language in the engagement process. In addition, to meaningfully incorporate the experiences and expertise of communities affected by TB, their engagement in the research process should occur as early as possible, ideally before research priorities and directions are set, and the scope of the research should encompass questions and outputs relevant to the community. Further, knowledge-sharing between researchers and the community should be ensured, not only of the research outputs but also regarding the engagement process itself, so that lessons learned can be carried forward. Lastly, the sustainability of community engagement processes (whether within institutions or projects) should be ensured, including through adequate funding for such engagement and the training, community mobilisation and relationship-building that this requires.